Knowledge and Application of Biosecurity Norms by Nursing Professionals in Intensive Care Units - Adonias Lubo Palma; Milagros Jiménez Flores; Ana Luisa Quevedo; María Montiel; Yadira Sirit; Maribel Petit (Kasmera, 2004)
In order to determine the knowledge and application of bio-security norms on the part of nursing professionals in the intensive care unit in a type IV public hospital in Zulia, a questionaire was applied to 60 professional nurses, and corroborated through direct observation of their daily activity. All had knowledge of biological risk factors and their supreme importance, and of preventative measures and their importance, however 76.66% identified erroneously the graveness of such risks. Also, they responded that the most frequent techniques used were hand washing and the use of gloves with ratings of 100% and 98.33% respectively. However, observation evidenced that the practice of handwashing before and after each procedure and between patients was only completed respectively by 10%, 53% and 10% respectively. The time employed in hand-washing was determined to be insufficient at less than one minute. Germicides were not used before sealing discarded cutting and puncturing devices, however 76.66% of them were deposited in appropriate containers. A low execution of compliance with immunization guidelines was observed. The results evidenced the need for continuing in-service education and strict supervision of the norms.